Regulatory contribution, tariff for radio spectrum And fee for commercial exploitation: tax aspects Of telecommunications - Soto Carrillo, Gerardo (2016)
The Peruvian government has stablished mandatory payments that telecom companies have to make: the regulatory contribution, the tariff for radio spectrum and the fee for commercial exploitation.In this article, the authors examine what tax nature and what validity basis those impositions have.